Provision of dental care in aged care facilities NSW Australia‐ Part 2 as perceived by the carers (care providers). (12th December 2013) - Webb, Bettine C; Whittle, Terry; Schwarz, Eli
Abstract : Objectives: To investigate carers' perception of the provision of dental care in aged care facilities (ACFs) New South Wales (NSW), Australia. Background: Carers are responsible for 'hands‐on, day‐to‐day' care of residents, including dental care, yet there were no specific figures available concerning their role in NSW ACFs. Materials and Methods: Questionnaires were mailed to 406 NSW directors of nursing (DONs) requesting completion by a carer who was proficient in English and without the influence of the DON. The 23‐item questionnaire was presented in 4 sections, and the data qualitatively analysed. Results: 211 questionnaires were completed and returned, giving a response rate of 52%. Carers were mostly female (91.9%) in the 40–50 and >50 age groups. Oral health training had been received by 66.7% of carers, and although 73.2% thought that their training was adequate, carers in general requested further training. Long waiting periods for government dental services (69.4%) and resident unable to communicate oral health problems (69.2%) were seen as the most frequent barriers to dental care. Almost all carers reported the availability of electric tooth brushes, fluoride gel, disclosing tablets/gel, interdental brushes and the use of a foam mouth prop, while few reported the use of other dental care products. Conclusion: As carers provided almost all of oral health care for residents, emphasis should be placed on training in geriatric dental care techniques and use of dental products.